2018
DOI: 10.1097/lbr.0000000000000458
|View full text |Cite
|
Sign up to set email alerts
|

1% Versus 2% Lignocaine for Airway Anesthesia in Flexible Bronchoscopy Without Lignocaine Nebulization (LIFE)

Abstract: One percent lignocaine in flexible bronchoscopy is as efficacious as 2% lignocaine when administered using the spray as you go technique without concurrent lignocaine nebulization, at a significantly lower total dose of lignocaine administered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Large RCTs in no-sedation bronchoscopy have been performed with pharyngeal anesthesia using lignocaine spray. [150151]…”
Section: Premedicationmentioning
confidence: 99%
“…Large RCTs in no-sedation bronchoscopy have been performed with pharyngeal anesthesia using lignocaine spray. [150151]…”
Section: Premedicationmentioning
confidence: 99%
“…However, 10% of pulmonologists and 12.5% of thoracic surgeons reported routine use of atropine. Randomized control studies have shown that the use of 1% lidocaine in “spray as you go” technique is effective and safe with significantly less total dose of lidocaine administered when compared to 2% lidocaine 19,20. In our survey, use of topical anesthetics deviated from the evidence to some extent.…”
Section: Discussionmentioning
confidence: 71%
“…Although, at the time of this study, we were routinely using nebulized lignocaine administration before EBUS-TBNA, the evidence to support nebulized lignocaine administration during bronchoscopy is weak. [ 4 ] All the EBUS-TBNA procedures in our study were performed through the oral route; therefore, the results may not be applicable to nasal route for performing the procedure. Nasal route has also been found safe and feasible to perform EBUS-TBNA though the requirement of lignocaine is likely to be higher in this case as nasal lignocaine gel application is additionally required.…”
Section: Discussionmentioning
confidence: 99%
“…Two large randomized controlled trials (RCTs) comparing 1% versus 2% lignocaine concentrations during flexible bronchoscopy (most procedures performed without sedation) have demonstrated equal efficacy of both concentrations for procedural satisfaction and cough suppression. [ 3 4 ] Performance of EBUS-TBNA with exclusive use of topical anesthesia is uncommon. [ 5 ] The available guidelines and expert panel report on technical aspects of EBUS-TBNA do not clarify the optimum lignocaine concentration for topical anesthesia during the procedure.…”
Section: Introductionmentioning
confidence: 99%